Rational design, fabrication, optical properties and high-efficiency visible-light photocatalytic degradation performance for organic pollutants of Eu:Bi2WO6/CdS nanostructures. Issue 4 (15th February 2022) - Zhang, Yiwen; Guo, Baogang; Feng, Wei; Li, Yuanli; Liu, Haifeng; Li, Renjie; Wu, Hongwei; Zhong, Xiaoyan; Ma, Guohua; Xie, Ruishi
Abstract: Over the past few years, semiconductor materials (especially bismuth tungstate) exhibiting unique environment purification and energy conversion capacities arouse huge attention as impacted by issues of environmental pollution and energy shortage, whereas its application is restricted by the problems of high carrier recombination rate and unsatisfactory degradation efficiency. In this study, Eu:Bi2 WO6 nanostructures containing Eu ions of different concentrations were synthesized with a chemical solution method, and CdS was generated on the surface of Eu:Bi2 WO6 nanostructures in situ epitaxial to synthesize the Eu:Bi2 WO6 /CdS composites. The effects of Eu doping concentration on the crystal structure, chemical composition, local structure, optical properties and visible-light photocatalytic properties exhibited by Eu:Bi2 WO6 /CdS nanostructures were studied more specifically, and the Eu doping behavior on the improvement mechanisms for optical and photocatalytic performance exhibited by Eu:Bi2 WO6 /CdS nanostructures was clarified. The robust PL emission peak at about 390 nm and weak emission peak at nearly 450 nm are attributed to the exciton emission and defect state of Bi2 WO6 /CdS nanostructure, respectively. As indicated from the mechanism insights, the reasonable introduction of Eu 3+ could alter the band gap of the photocatalyst, and the epitaxial CdS could decrease the recombination probability of electron and hole in the Bi2 WO6 /CdS, while improving the photocatalytic activity. This study supplies new occasions for rational excogitation and better comprehending of atomic-scale complicated structures for applications in numerous fields (e.g., energy and environmental protection).